Valor nutricional e capacidade antioxidante de diferentes genótipos de amora-preta (Rubus sp.) - Hirsch, Gabriela Elisa (2011)
Rio Grande do Sul is among the major blackberry (Rubus sp.) producer states from Brazil, but studies evaluating this fruit in Brazil are scarce. Thus, this study was aimed at determining the nutritional characteristics and bioactive compounds of different blackberry genotypes from Rio Grande do Sul, as well as their antioxidant capacity. The blackberry genotypes (selections 07/001, 03/001, 02/96 and 99 and cultivars Guarani, Cherokee, Tupy and Xavante) evaluated were cultivated at Embrapa Temperate Climate (Pelotas, RS, Brazil, 31o40‟47‟‟S, 52o26‟24‟‟W, 60 m). The fruits had 84.8 - 90.3% humidity, 0.09 - 0.14% protein, 5.8 - 5.5% dietary fiber and 0.27 - 0.49% ash. Selection 02/96 had the lowest ash content. TSS ranged from 7.3 to 10.2 °Brix, acidity ranged between 1.30 and 1.58% citric acid and pH between 2.8 and 3.1. Selection 03/001 had the lowest TSS value and it also had lower redness, but higher color saturation than Tupy cultivar. Selection 03/001 showed more intense and brighter color than the other genotypes. The fatty acids found at higher concentration were palmitic (22-29%), oleic (13-32%) and linoleic (15-33%) acids, with small differences among the blackberry genotypes. Four different antioxidant assays were conducted to assess the antioxidant activity of both phenolic and anthocyanic fruit extracts. Regarding the phenolic extracts, selections 02/96 and 07/001 had higher antioxidant activity than the cultivars in most assays, and this activity was partially correlated to the higher amount of total phenolics in these samples. Thus, the phenolic compounds are probably the major responsible for the antioxidant activity in the diphenyl-2-picrylhydrazyl radical scavenging assay (DPPH), ferric-reducing antioxidant power assay (FRAP) and thiobarbituric acid reactive substances assay (TBARS). Quercetin seems to be responsible for the antioxidant activity of blackberry phenolic extracts in the β-carotene bleaching assay. Concerning the anthocyanic extracts, selection 02/96 and Tupy and Cherokee cultivars from harvest 2007 had higher antioxidant activity than the other genotypes in most assays. Anthocyanins appear to be the major responsible for the antioxidant activity of anthocyanic extracts in the DPPH and FRAP assays, although ascorbic acid also contributed to the DPPH antioxidant activity. It was not possible to identify the compound responsible for the TBARS antioxidant activity of anthocyanic extracts. Our results revealed that the new blackberry selections developed by Embrapa, especially selection 02/96 appears to have higher antioxidant activity than the commercial cultivars cultivated in the southern Brazil. Thus, this selection appears to be promising for nutritional and health purposes. Furthermore, the blackberry genotypes evaluated had good nutritional value with sugar and acidity levels suitable for industrialization, and they contain fatty acids important for maintaining health.